The Effect of Going-Concern Audit Opinion on Market Reaction: Evidence from Indonesia - Meita Rahmawati, Agil Novriansa, (Opción, 2019)
This study aims to examine the effect of the going-concern audit opinion on market reaction. This study used the event study methodology with 120 days estimation period and 31 days window period. The results of the Wilcoxon signed rank test shows that there is a significant statistical difference in the average abnormal returns between before and after going-concern audit opinion disclosure. It means that going-concern audit opinion has an effect on the market reaction. In conclusion, negative market reaction is indicated by the tendency of decreasing abnormal return value of the stock to negative after disclosure of going-concern audit opinion.